Predictors of intention to turnover in behavior technicians working with individuals with autism spectrum disorder. (September 2015) - Kazemi, Ellie; Shapiro, Marnie; Kavner, Alyssa
Highlights: Employee turnover has deleterious effects on clinical services and is costly for employers. We conducted a survey of BTs who work with individuals with ASD. Level of satisfaction with training, supervision, pay, and different aspects of the job itself predicted BTs' intent to turnover. Actual pay did not correlate with satisfaction with pay or intent to turnover. In the future, researchers should experimentally evaluate methods to decrease voluntary employee turnover. Abstract: Employee turnover has deleterious effects on clinical services such that it hinders service quality, damages the therapeutic relationship, and compromises company infrastructure. However, little is known about predictors of turnover for behavior technicians (BTs) who implement behavioral interventions with individuals with autism. Therefore, the aim of this study was to identify factors that serve as predictors of intention to turnover and provide a bedrock for direct assessment of strategies to reduce turnover among BTs. A total of 96 BTs from 19 different agencies in Southern California completed the entire online survey. We found that level of satisfaction with training, supervision, and pay (not their actual hourly pay), along with satisfaction with different aspects of the job (e.g., opportunities for advancement, praise for doing a good job) predicted BTs' intent of turnover. We discussed the potential implications of our findings for researchers interested in examining methods to minimize turnover and increase continuity of behavioral care for individuals with autism spectrum disorders.